Entrepreneurial continuance logic: The interplay between climate, commitment, and entrepreneurial responsiveness. Issue 7 (23rd November 2018) - Datta, Pratim; Peck, Jessica Ann; Koparan, Ipek; Nieuwenhuizen, Cecile
Abstract : Purpose: While much has been debated about venture formation and demise, the behavioral dynamics of why entrepreneurs intend to continue and persevere post-startup have received scant attention and scrutiny. Building upon the rich tapestry of entrepreneurial cognition, the purpose of this paper is to forward entrepreneurial continuance logic as a theoretical framework to empirically investigate the antecedents, contingencies and mediators of entrepreneurial continuance. Design/methodology/approach: Using observations from surveying 156 practicing entrepreneurs across the USA, UK, South Africa and India, this research offers interesting findings. Findings: Results surface attitudinal tensions between the transactional attitudes of entrepreneurial climate, entrepreneurial responsiveness and calculative commitment and the relational attitudes of affective and normative continuance. Specifically, the authors find that affect is the strongest direct predictor of continuance intentions but only in the absence of entrepreneurial responsiveness behavior. Research limitations/implications: Entrepreneurial responsiveness, rather than commitment, is found to be a core continuance constituent, traceable as a positive influence on continuance as a direct antecedent, a moderator and a mediator. Practical implications: The research reveals that entrepreneurs willing to seize and adapt to a changing entrepreneurial landscape are more like to continue with their ventures, but not just driven by strict underpinnings of affect and norms but by a strong sense of economic rationality. Social implications: Entrepreneurial continuance is an important behavioral phenomenon with substantial socio-economic consequences. Given the scant attention paid to entrepreneurial continuance – symptomatic of broader downstream effects of entrepreneurial survival and positive socio-economic spillovers, the authors embark on a systematic investigation of continuance intention as post-startup behavior. Originality/value: The paper explains post-startup entrepreneurial behavior in several ways. First, while affective commitment, a relational attitude, still drives continuance intentions, calculative commitment, a transactional attitude, is a significant contender. Interestingly, the nature of contemporary entrepreneurship disregards continuance behavior based on norms. Second, entrepreneurial responsiveness needs to be cautiously examined in relationship to commitment and continuance. Entrepreneurial responsiveness, a transactional attitude, positively influences continuance; however, in the presence of a relational attitude such as affective commitment, the interplay reduces continuance intentions. Third, perceptions of entrepreneurial climate are found to trigger more opportunity-seeking behavior among entrepreneurs, which in turn increases an entrepreneur's intention to continue.